8-hydroxyquinoline-glucuronide Sodium Salt Used as Electroactive Substrate for a Sensitive Voltammetric Detection of Escherichia Coli in Water Samples. (2016) - Ettenauer, Jörg; Zuser, Karen; Kellner, Karlheinz; Posnicek, Thomas; Brandl, Martin
Abstract: Escherichia coli are fecal indicator organisms and can represent a serious health hazard. The aim of our study was the development of a new and simple electrochemical method for a fast and sensitive detection of E. coli . Therefore, the β-D-glucuronidase (GUS) enzyme production was stimulated. The GUS activity promoted the cleavage of a specific substrate into an electroactive compound that was oxidized using a potentiostat leading to a signal in a specific current output range. The principle of the assay was tested with enzyme solutions before living cells were investigated. The output signal was continuously measured, indicated enzyme activity and subsequently, was an evidence for E. coli cells. After verification of the methodology, we were able to specifically detect one colony-forming unit per ml within 10 h. The developed method comprises of only a few working steps and allowed a sensitive identification without any interference from other bacteria.